Reinforcing or moderating? The impact of Brexit on Italian and German Euroscepticism - Orlando, Vittorio; Conrad, Maximilian (Frontiers in Political Science, 2024)
This article investigates the impact of Brexit on Eurosceptic parties' arguments for leaving (or remaining in) the European Union (EU). Drawing on a comparative design, the article looks at the images and narratives of the EU that Eurosceptic parties in Italy and Germany have advanced in the aftermath of the 2016 Brexit referendum and reflects on the broader implications in terms of the prospects of further states leaving the EU. This research is motivated by two assumptions grounded in the literature on Euroscepticism and EU polity contestation: firstly, that Euroscepticism is fuelled by external circumstances that are exploited by interested political actors; and secondly, that both the Brexit referendum and the UK's departure from the EU have had a profound impact on discourses on the EU within member states, most importantly because this process has highlighted the real possibility of replacing EU membership with trade agreements and other specific arrangements.Germany after Brexit, the article reveals that on the structural level, Eurozone membership remains the main obstacle to leaving the EU. Yet on the ideological level, Eurosceptic discourse in the two countries centres on two principles that are at odds with each other. Beyond the alleged lack of democratic representation within EU institutions that is pointed out by Eurosceptic parties in both countries, the main criticism of the EU project in Germany is that the country shares the costs of states with lower economic outputs. In Italy, on the other hand, the criticism is that the EU benefits wealthier states while constraining the country's opportunities for development.